Juridical Analysis of the Validity of the Bachelor's Degree of the 7th President of Indonesia, Joko Widodo, in a Defamation Case Study - Verdinandus Kiki Affandi; Wisnu Aryo Dewanto (Universitas Muhammadiyah Mataram, 2025)
This article examines the validity of the undergraduate diploma of Indonesia’s 7th President, Joko Widodo, within the context of defamation offenses under Indonesian criminal law. The main focus of this study is to analyze whether allegations of diploma forgery disseminated to the public can be classified as defamation, and to explore the evidentiary mechanisms in such cases. The research adopts a normative juridical approach by analyzing relevant legislation, including the Indonesian Penal Code (KUHP) and the Electronic Information and Transactions Law (ITE Law), as well as reviewing the law enforcement processes involving allegations against public officials. The findings indicate that accusations directed at the President concerning a forged diploma may constitute defamation if not supported by valid evidence. The evidentiary process in such cases involves official documents, testimonies from related parties, and digital traces of the dissemination of the allegations. This study also provides recommendations for more transparent and prudent law enforcement in addressing defamation cases in the digital era.